Studying targeted oxidation in diabetic cognitive dysfunction based on scientometrics analysis: research progress of natural product approaches - Tu, Wenling; Xu, Fuhang; Li, Jieying; Tian, Xiangfeng; Cao, Lingyong; Wang, Lei; Qu, Yiqian (Frontiers in Endocrinology, 2024)
The aim is to provide new insights for researchers studying the pathogenesis of diabetic cognitive dysfunction and promoting the wider use of natural products in their treatment.Method: First, the Web of Science Core Collection was selected as the data source for a computerized literature search on oxidative stress and diabetic cognitive dysfunction (DCD). Next, Biblimetrix and VOSviewer performed statistical analysis focusing on publication countries, institutions, authors, research hotspots, and emerging directions in the field.Then, through the analysis of keywords and key articles, the forefront of the field is identified. Finally, we discussed the pathogenesis of DCD, the influence of oxidative stress on DCD and the antioxidant effect of natural products on DCD.Result: 293 valid papers were obtained. Bibliometrics showed that oxidative stress, diabetes, Alzheimer's disease (AD), cognitive decline, insulin resistance and quercetin were the key words of the symbiotic network.The antioxidant effects of natural products in improving DCD have been extensively studied in preclinical studies, providing potential for their treatment in DCD, but their evaluation in clinical trials is currently uncommon.